Based on mother and child protection card, awareness and practices among Mitanins and auxiliary nurse midwife workers about obstetric care: will repeated drilling be the game changer? - Armo, Meena; Sainik, Siddhi; Thakur, Ekata; Biswas, Anamika; Gupta, Khushal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: More than 70,000 women community health volunteers called the ‘Mitanins’ and auxiliary nurse midwife (ANM) are working for the improvement of the health care system in the state. The study was undertaken to assess the knowledge and practices among Mitanins and ANMs regarding antenatal care including risk identification , purely based on MCP card to help health professionals to make necessary changes in the MCP card, and revise maternal health policies and practices. Methods: It was a cross-sectional questionnaire-based study, conducted from November 2020 to October 2021 in the department of obstetrics and gynecology at government medical college, Rajnandgaon. This was the only government tertiary care hospital in southwest Chhattisgarh of that time. A total of 22 ANMs and 166 Mitanins were included and assessed. Based on the MCP card predesigned, pretested questionnaires were made and used. ASPSS 21.0 version software was used to analyze the data. Results: Total 166 Mitanins and 22 ANMs were participated in the study. Overall knowledge of participants about antenatal, intra-natal and postnatal care services was poor. None of them were aware of what low-risk or high-risk pregnancy is. Mitanins were not familiar with any of the medical terms or obstetric complications mentioned on the MCP card while ANMs were quite aware of it, however the percentage was negligible (<10%). Moreover, knowledge about obstetrics examination and per vaginum examination was very poor (13.6%) among ANMs. Knowledge about danger signs related to obstetric emergencies which are not mentioned on the MCP card for example, ectopic pregnancy, vesicular mole, obstructed labor, impending scar rupture, and uterine rupture was also very low (<15%) among Mitanins and ANMs. Conclusions: The language and understandability of the MCP card need to be addressed. The gap between knowledge and practice can be bridged by proper ‘training’.